ประสิทธิภาพของจิบเบอเรลลินในการส่งเสริมการเจริญเติบโตของยอดอ่อนทุเรียน (Durio zibethinus) พันธุ์หมอนทอง - ประทุมยศ วิกันยา; จิตร์อารี เลิศชัย; ชคตระการ สมชาย (Thai Journal of Science and Technology, 2020)
The management of durian leaves for high quality and quantity is an important step for off-season durian production. Therefore, the objective of this research was to study the efficiency of gibberellin to enhance the growth of young durian shoot var. ‘Monthong’. Sixteen durian seedlings were selected and transplanted. Seven days after transplanting, durian seedlings were sprayed 1 time with 30 mL of water (control) and gibberellin at the concentrations of 250, 500 and 750 ppm for each plant. The results showed that the height increment per durian seedling, height increment per young shoot, leaf number per young shoot, total leaf area of young shoot, fresh and dry weights per young shoot, nitrogen and phosphorus contents of seedlings treated with gibberellin at the concentrations of 500 and 750 ppm were significantly higher than those of the control treatment. There was no significant difference in The results indicated that gibberellin could promote the growth of young durian shoot var. ‘Monthong’.